Tradeoffs, balancing, and adaptation in the agriculture-oil and gas nexus: Insights from farmers and ranchers in the United States. (January 2019) - Haggerty, Julia H.; Smith, Kristin K.; Weigle, Jason; Kelsey, Timothy W.; Walsh, Kathryn Bills; Coupal, Roger; Kay, David; Lachapelle, Paul
Abstract: This paper seeks to expand an emerging, multi-disciplinary body of work about tradeoffs in the agriculture-oil and gas nexus by offering evidence of the ways that farm and ranch operators experienced and negotiated costs and benefits of hosting oil and gas in three U.S. oil and gas plays. We report results of mail survey sent to landowners in four rural counties in three U.S. oil and gas regions (Marcellus, Powder River Basin and Bakken) and specifically data from farmers and ranchers about perceptions and experiences of the agriculture-oil and gas nexus (n = 96). The data provided through closed- and open-ended questions suggest, from the perspective of those hosting energy infrastructure on farms and ranches, oil and gas development has enhanced agriculture operations and rural livelihoods but is not without negative impacts or tradeoffs. We introduce the balancing act as a useful framework for considering tradeoffs associated with hosting extractive industries as it allows space for the "balance" between economic activities to be impossible, aspirational or achievable. The study observes that mechanisms through which positive and negative effects operate vary according to agricultural context. Implications for research and practice in the agriculture-energy nexus are discussed.